Individualized pleasure-oriented exercise sessions, exercise frequency, and affective outcomes: a pragmatic randomized controlled trial - Diogo S. Teixeira; Vasco Bastos; Ana J. Andrade; António L. Palmeira; Panteleimon Ekkekakis (BMC, 2024)
Abstract Background Affective responses are increasingly recognized as potentially effective intervention targets that may facilitate exercise and physical activity behavior change. While emerging correlational evidence suggests that more pleasant affective responses are associated with higher participation and adherence, experimental evidence remains scarce. In light of this, we conducted a preregistered, pragmatic, single-blinded, superiority randomized controlled trial with two parallel groups, with the goal of determining the impact of an individualized exercise-intensity prescription targeting pleasure on exercise frequency. Methods Forty-seven non-regular exercisers were randomized into two groups. For both groups, the intervention consisted of three exercise sessions based on the Frequency-Intensity-Time-Type (FITT) principle. However, the experimental group also received an individualized intensity prescription based on prior assessment of preference for and tolerance of exercise intensity, as well as instructions emphasizing the promotion of pleasure as a basis for self-regulating exercise intensity. The primary outcome was gymnasium attendance over an eight-week follow-up period. Secondary outcomes were affective valence and arousal, post-exercise enjoyment, core affective exercise experiences, and anticipated and remembered affect. Results Forty-six participants were retained for analysis (Mage = 32.00; SD = 8.62 years; 56.5% female). Compared to the control group, the experimental group exhibited 77% higher session attendance (14.35 vs. 8.13 sessions) over the eight-week follow-up period (group main effect p = 0.018, η2 p = 0.120; Cohen's d ranged from 0.28 to 0.91 during follow-up). Also, the experimental group reported higher levels of pleasure during the intervention sessions (for all group main effects, p < 0.001, η2 p from 0.33 to 0.37) and higher levels of remembered pleasure (group main effect p = 0.021, η2 p = 0.116) and anticipated pleasure (group main effect p = 0.022, η2 p = 0.114). No harm was detected. Conclusions These results demonstrate the practicality and effectiveness of an intervention aimed at enhancing affective responses to exercise in improving short-term session attendance. Trial registration ClinicalTrial.gov NCT05416593.